1999
DOI: 10.1139/e98-080
|View full text |Cite
|
Sign up to set email alerts
|

A model for induced seismicity caused by hydrocarbon production in the Western Canada Sedimentary Basin

Abstract: Over the past three decades, a significant number of small-magnitude and shallow earthquakes have occurred in the Western Canada Sedimentary Basin and are located along its western flank near areas of oil and gas production. One of the better documented examples is the swarm of earthquakes associated with the Strachan field, in the Alberta foothills. A model based on Segall's poroelastic theory is developed to account for the occurrence of earthquakes below the Strachan reservoir. Using this methodology, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…Over time, the extensional zones migrate further outward and compressive zones further down. Consequently, reverse faulting is favored above and below the reservoir, while normal faulting is favored along the flanks of the reservoir [38][39][40][41] (Figure 8). The normal fault associated to the M w 6.5 Botswana earthquake is located more than 20 km below the CBM reservoir, where the potential anthropogenic stress changes are compressive and thrust faulting is privileged with respect to normal faulting.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the extensional zones migrate further outward and compressive zones further down. Consequently, reverse faulting is favored above and below the reservoir, while normal faulting is favored along the flanks of the reservoir [38][39][40][41] (Figure 8). The normal fault associated to the M w 6.5 Botswana earthquake is located more than 20 km below the CBM reservoir, where the potential anthropogenic stress changes are compressive and thrust faulting is privileged with respect to normal faulting.…”
Section: Discussionmentioning
confidence: 99%
“…A M L 3.8 earthquake southwest of Rocky Mountain House also occurred on 9 August 2014 near previously documented induced earthquakes [Wetmiller, 1986;Baranova et al, 1999;Stern et al, 2013], although the event was not spatially or temporally correlated with any reported hydraulic fracturing activity [Baranova et al, 1999]. We use the 9 August 2014 earthquake and seven other similar events recorded in the AC catalog to construct five templates for each channel of station TD012 ( Figure S4 in the supporting information).…”
Section: Matched-filter Approachmentioning
confidence: 98%
“…The assessment of the potential hazard for these triggered or induced earthquakes has become a relevant and pressing problem, especially because seismicity rates have increased in some locations. In the Western Canada Sedimentary Basin, seismic activity has been conjectured as being induced by hydraulic fracturing (Farahbod et al 2015;Schultz et al 2015a), gas extraction (Baranova et al 1999) or waste water disposal (Horner et al 1994;Schultz et al 2014). Fracking operations in the United Kingdom were stopped for several years after the detection of two earthquakes with magnitudes of M L 2.3 and 1.5 in the Blackpool area (Clarke et al 2014).…”
Section: Introductionmentioning
confidence: 99%